EXAMINING THE EFFECTIVENESS OF CLUSTERING TECHNIQUE IN TEACHING WRITING RECOUNT TEXT - Natalia Anggrarini; Intan Ali Indah; Kardi Nurhadi (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Writing is the skill of conveying ideas in written form that can be understood, and the meaning of writing can be conveyed. However, writing is also difficult to master and learn at all levels, as it requires a lot of thought to generate ideas and produce words and sentences. Therefore, researchers use this clustering technique as a learning method before writing activities to design ideas that support the writing of their texts. The main objective of this study was to determine the effectiveness of the clustering technique in teaching writing recount text. The researcher used quantitative research and pre-experimental research as the research design. This research was conducted in class X-1 MIPA at SMAN 2 Indramayu. For the data collection, the researcher used cluster sampling. From the results, it was found that the results of the students' pre-test scores obtained a total score of 2050, and the students' post-test scores obtained a total score of 2750 with a gain score of 700. This means that there is an increase in the quality of students. . The results of the statistical hypothesis showed a value of up to 834 and a critical value of 1.69. Compared with the to and tcritic calculations, it shows that the value of to > tc or 8.34 > 1.69, then rejects H0. So, because H0 is rejected, the clustering technique is effective to achieve the target of increasing the effectiveness of learning to write recount text. This research implies that teaching writing must use certain techniques/methods/strategies and pay attention to the aspects of the criteria used so that students can develop ideas and produce better writings. The researchers suggest the teachers to use various creative techniques/methods/strategies that can help the students get new ideas in learning to write English, especially in recount text.